Coupling molecular spin centers to microwave planar resonators: towards integration of molecular qubits in quantum circuits. Issue 42 (28th July 2016) - Bonizzoni, C.; Ghirri, A.; Bader, K.; van Slageren, J.; Perfetti, M.; Sorace, L.; Lan, Y.; Fuhr, O.; Ruben, M.; Affronte, M.
Abstract : Strong coupling meets coordination chemistry: hints in the design of molecular qubits in hybrid quantum circuits. Abstract : We present spectroscopic measurements looking for the coherent coupling between molecular magnetic centers and microwave photons. The aim is to find the optimal conditions and the best molecular features to achieve the quantum strong coupling regime, for which coherent dynamics of hybrid photon-spin states take place. To this end, we used a high critical temperature YBCO superconducting planar resonator working at 7.7 GHz and at low temperatures to investigate three molecular mononuclear coordination compounds, namely (PPh4 )2 [Cu(mnt)2 ] (where mnt 2− = maleonitriledithiolate), [ErPc2 ] − TBA + (where pc 2− is the phtalocyaninato and TBA + is the tetra- n -butylammonium cation) and Dy(trensal) (where H3 trensal = 2, 2′, 2′′-tris(salicylideneimino)triethylamine). Although the strong coupling regime was not achieved in these preliminary experiments, the results provided several hints on how to design molecular magnetic centers to be integrated into hybrid quantum circuits.